2017
DOI: 10.1111/ppa.12740
|View full text |Cite
|
Sign up to set email alerts
|

Plant age and ambient temperature: significant drivers for powdery mildew (Erysiphe cruciferarum) epidemics on oilseed rape (Brassica napus)

Abstract: Powdery mildew (Erysiphe cruciferarum) is an important disease in oilseed rape crops worldwide, but of sporadic importance in most southern Australian crops. Six Brassica napus cultivars were exposed to E. cruciferarum simultaneously in four plant age cohorts. First symptoms of powdery mildew appeared 9 days after inoculation (dai) on the oldest plants [42 days after seeding (das)], but 44 dai in the youngest plants that were exposed to inoculum from sowing, although final disease severity did not differ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…Manning & Tiedemann, ; Rosenzweig et al , ). Other Australian studies on rapeseed have demonstrated more severe disease under warmer rather than cooler temperatures, including for H. brassicae (Mohammed et al , ), Erysiphe cruciferarum (Uloth et al , ) and L. maculans (Barbetti, ; Li et al , ). The present study with isolates collected in 2016 across three states of Australia highlights distinct overall differences in terms of virulence between the states.…”
Section: Discussionmentioning
confidence: 95%
“…Manning & Tiedemann, ; Rosenzweig et al , ). Other Australian studies on rapeseed have demonstrated more severe disease under warmer rather than cooler temperatures, including for H. brassicae (Mohammed et al , ), Erysiphe cruciferarum (Uloth et al , ) and L. maculans (Barbetti, ; Li et al , ). The present study with isolates collected in 2016 across three states of Australia highlights distinct overall differences in terms of virulence between the states.…”
Section: Discussionmentioning
confidence: 95%
“…Such impacts include changes of temperature, rainfall, and humidity, the main drivers of plant disease severity. For example, the expression of some Brassica resistance genes against pathogens are temperature dependent, including blackleg (Li et al, 2006b), TuMV (Nyalugwe et al, 2014), Sclerotinia (Uloth et al, 2015c), powdery mildew (Uloth et al, 2018), and downy mildew epidemics in B. juncea and B. napus (Mohammed et al, 2018a). Li et al (2006a) argued that resistance against sclerotinia stem rot may not be currently necessary for B. juncea due to its optimal cultivation in low rainfall regions, where the conditions are less favourable for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Such impacts include changes of temperature, rainfall, and humidity, the main drivers of plant disease severity. For example, the expression of some Brassica resistance genes against pathogens are temperature dependent, including blackleg (Li et al, 2006b), TuMV (Nyalugwe et al, 2014), Sclerotinia (Uloth et al, 2015c), powdery mildew (Uloth et al, 2018), and downy mildew epidemics in B . juncea and B .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations